Author Correction: Genomic analysis of a large set of currently—and historically—important human adenovirus pathogens. Issue 1 (December 2018) - Ismail, Ashrafali; Cui, Tiange; Dommaraju, Kalpana; Singh, Gurdeep; Dehghan, Shoaleh; Seto, Jason; Shrivastava, Susmita; Fedorova, Nadia; Gupta, Neha; Stockwell, Timothy; Halpin, Rebecca; Madupu, Ramana; et al.
The original publication of this article [1] was missing the below author that made contributions to the research and the published article: